Enhanced photocatalytic degradation of azo dye in aqueous solutions using Ba@Ag@ZnO nanocomposite for self-sensitized under sunshine irradiation. (23rd February 2017) - Dhatshanamurthi, P.; Shanthi, M.
Abstract: The aqueous solutions of Trypan blue (TB) textile dye are totally mineralized when irradiated with prepared photocatalyst under sunshine. The intensity of the sunshine was measured using Lux meter. The prepared catalyst of barium loaded Ag@ZnO (Ba@Ag@ZnO) was successfully synthesized by the precipitation–decomposition process aided by ultrasound method. The catalyst was characterized by X-Ray Diffraction (XRD), Field Emission Scanning Electron Microscope (FESEM), Energy Dispersive Spectrum (EDS), Transmission Electron Microscope (TEM), Diffuse Reflectance Spectra (DRS), Photoluminescence spectra (PL) and BET surface area measurements. The Ba@Ag@ZnO is found to be more efficient than Ag@ZnO, Ba@ZnO, commercial ZnO and bare ZnO at pH 7 for the mineralization of Trypan Blue dye. The effects of operational parameters such as the amount of photocatalyst, dye concentration, initial pH on photo mineralization of TB dye have been analyzed. The mineralization of TB has been confirmed by Chemical Oxygen Demand (COD) measurements and hydroxyl method. The results showed that the dye molecules were completely degraded to CO2 and H2 O under sunshine irradiation. It is accomplished that sunshine induced poverty of textile dye in wastewater is a viable technique for wastewater treatment. Graphical abstract: Highlights: The new barium-loaded silver@Zinc oxide was successfully synthesised by precipitation–decomposition process aided by ultrasound method. This new method of preparation gives a homogeneous dispersion of Ba-loaded on Ag@ZnO. The catalyst is found to be reusable. Treatment of various dye effluent using Ba-loaded Ag@ZnO will be more economical and environmental. The presence of dye mechanism for the squalor also has been proved.